Kepastian Hukum Terhadap Eksistensi dan Implementasi Justice Colaborator dalam Pemberantasan Tindak Pidana Korupsi Di Indonesia - Susanti, Evy; Suparji, Suparji; Rifai, Anis (Jurnal Bedah Hukum, 2025)
Justice collaborators (JC) and whistleblowers are parties or legal subjects involved in the occurrence of a corruption crime. The existence of the JC is intended to help uncover the facts of corruption crimes. In reality, the JC has no legal certainty in determining the most responsible party and there is no clarity about the considerations in granting the JC. The purpose of this study is to find out the existence of justice collaborators in corruption crimes. This type of research is normative juridical with analytical descriptive nature. The conclusion in this study is that the existence of JC can shed light on a corruption crime in Indonesia, because their role can reveal the perpetrators or masters of mind or the perpetrators who have the most major contribution to the crime. In order to provide legal certainty, there needs to be comprehensive regulatory clarity on JC.